Fusaricidins from Paenibacillus polymyxa M‐1, a family of lipohexapeptides of unusual complexity—a mass spectrometric study. (22nd November 2016) - Vater, Joachim; Herfort, Stefanie; Doellinger, Joerg; Weydmann, Max; Dietel, Kristin; Faetke, Sebastian; Lasch, Peter
Abstract : Paenibacillus polymyxa are rhizobacteria with a high potential to produce natural compounds of biotechnological and medical interest. Main products of P . polymyxa are fusaricidins, a large family of antifungal lipopeptides with a 15‐guanidino‐3‐hydroxypentadecanoic acid (GHPD) as fatty acid side chain. We use the P . polymyxa strain M‐1 as a model organism for the exploration of the biosynthetic potential of these rhizobacteria. Using matrix‐assisted laser‐desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF MS) about 40 new fusaricidins were detected which were fractionated by reversed‐phase (rp) HPLC. Their structure was determined by MALDI‐LIFT‐TOF/TOF fragment analysis. The dominant fragment in the product ion spectra of fusaricidins appeared at m / z 256.3, 284.3 and 312.4, respectively, indicating variations in their fatty acid part. Two new subfamilies of fusaricidins were introduced which contain guanidino‐3‐hydroxyhepta‐ and nonadecanoic acid as fatty acid constituents. Apparently, the end‐standing guanidine group is not modified as shown by direct infusion nano‐electrospray ionization mass spectrometry (nano‐ESI MS). The results of this study suggest that advanced mass spectrometry is the method of choice for investigating natural compounds of unusual diversity, like fusaricidins. Copyright © 2016 John Wiley & Sons, Ltd.